Serum estradiol (E2), progesterone (P), and human chorionic gonadotropin (HCG), D-dimer (D-D) fibrinogen (FIB) levels after Low Molecular Weight Heparin Sodium on Preventing Miscarriage in Patients with Adverse Pregnancy and Delivery: Serum E2, P, HCG, D-dimer , fibrinogen in Adverse Pregnancy - Pei, Liucheng (Journal of Medical Biochemistry, 2025)
Introduction: It was to investigate the effect of subcutaneous injection of low molecular weight heparin (LMWH) sodium on preventing miscarriage in patients with adverse pregnancy and childbirth and on Serum estradiol (E2), progesterone (P), and human chorionic gonadotropin (HCG), D-dimer (D-D) fibrinogen (FIB) levels. Material and Method: Eighty-two patients with adverse pregnancy admitted to Wuhai Maternal and Child Health Hospital from April 2024 to December 2024 were randomly grouped, 41 cases in each group. Controlgroup(CG) adopted dydrogesterone, and observation group (OG) adopted subcutaneous injection of LMWH sodium on this basis. The sex hormones, pre-thrombotic state (PTS) indexes, and application effects were compared between two groups before and after treatment. Result: progesterone (P), Estradiol (E2), and human chorionic gonadotropin (HCG) in OG were higher as against CG (P
Keywords: Serum estradiol (E2), progesterone (P), and human chorionic gonadotropin (HCG), D-dimer (D-D) fibrinogen (FIB) levels ,LMWH sodium; adverse pregnancy and childbirth; tocolysis; PTS